A new challenge to ethical codes: Heart transplants - Wright, Irving S. (Journal of religion and health, 1969)
We have entered into a new era of medical achievement with the development of successful transplantation of human organs. The transplantation of the heart has aroused the greatest scientific interest and at the same time created serious new problems of an ethical and legal nature. It has been necessary to develop new criteria to determine the "moment of death" of the donor in order to ensure continued life for the recipient. The decision of the moment of death should be made by a small team of skilled physicians interested in furthering this important development, but not as emotionally involved as are the surgeons awaiting the chance to prolong their patient's life with a new heart. Available and suitable hearts will probably always be in very short supply, and the selection of recipients will therefore become critical if the procedure proves to be widely acceptable.New laws will be essential before this process can be adopted in many states and countries. The cost in terms of total resources is so large that careful evaluation of the long-term results must be undertaken after a reasonable number of patients have been operated on and observed, perhaps at the end of the second year following the first procedure. Since the cost of each operation of this type approximates that of the education of several young physicians who could care for thousands of patients during their life span, a good hard look at the potential benefits and ultimate values is in order. At this point in time it is extremely important that this type of surgery be encouraged but limited to those prepared to undertake it with maximum skill and minimal risk. At present it must be recognized as a great experiment rather than a therapeutic triumph for general application.